Towards an applied metaecology - Schiesari, Luis; Matias, Miguel G.; Prado, Paulo Inácio; Leibold, Mathew A.; Albert, Cecile H.; Howeth, Jennifer G.; Leroux, Shawn J.; Pardini, Renata; Siqueira, Tadeu [UNESP]; Brancalion, Pedro H.S.; Cabeza, Mar; Coutinho, Renato Mendes; et al. (Elsevier, 2019)
The complexity of ecological systems is a major challenge for practitioners and decision-makers who work to avoid, mitigate and manage environmental change. Here, we illustrate how metaecology – the study of spatial interdependencies among ecological systems through fluxes of organisms, energy, and matter – can enhance understanding and improve managing environmental change at multiple spatial scales. We present several case studies illustrating how the framework has leveraged decision-making in conservation, restoration and risk management. Nevertheless, an explicit incorporation of metaecology is still uncommon in the applied ecology literature, and in action guidelines addressing environmental change. This is unfortunate because the many facets of environmental change can be framed as modifying spatial context, connectedness and dominant regulating processes - the defining features of metaecological systems. Narrowing the gap between theory and practice will require incorporating system-specific realism in otherwise predominantly conceptual studies, as well as deliberately studying scenarios of environmental change.
Keywords: Applied ecology; Conservation; Ecology; Metacommunity; Metaecosystem; Metapopulation